Risk relationship between leukocyte telomere length and constipation: a Mendelian randomization study - Chi, Zhenfei; Bai, Xuesong; Zhang, Zhe (Frontiers in Medicine, 2023)
Objective: There exist some epidemiological studies investigating the associations between aging and constipation, yet their outcomes are inconclusive, so we strive to ascertain whether aging is the cause of constipation. Methods: We conducted a two-sample Mendelian randomization analysis using publicly accessible genome-wide association studies summary statistics. As a marker of cellular and biological aging, we employed fifteen single-nucleotide polymorphisms (SNPs) as instrumental variables for leukocyte telomere length as exposure, and a genome-wide association study for constipation in the Finnish database as an outcome. To select the instrumental variables strongly associated with the phenotype, we eliminated confounding factors and direct effects outcomes to determine the causal relationship of exposure factors on the outcome; the analysis was mainly performed using the random-effect inverse variance weighting method, MR-Egger, weighted median, and a sensitivity analysis of the results. Results: Random effect inverse variance weighted OR = 1.035 (95%CI 0.907-1.180), but p=0.612, not statistically significant; Other statistical methods, such as MR-Egger and weighted median, also yielded non-significant results. Conclusion: LTL as a proxy for aging does not necessarily indicate an increased likelihood of constipation. Further research is needed to explore the specific mechanisms of constipation.